Bedtime blues : suds ,soaps, and shells. - Mignot Laurent (AG Aurora production, 2012)
A three-part book and video animation combo series. Character-building stories for children featuring fun Dino friends. Two stories in each book with 3-D style artwork; DVD in the cover. Values include: healthy habits, honesty, forgiveness.